Template for using biological trait groupings when exploring large‐scale variation in seafloor multifunctionality. Issue 1 (6th December 2017) - Villnäs, Anna; Hewitt, Judi; Snickars, Martin; Westerbom, Mats; Norkko, Alf
Abstract: Understanding large‐scale spatial variation in ecosystem properties and associated functionality is key for successful conservation of ecosystems. This study provides a template for how to estimate differences in ecosystem functionality over large spatial scales by using groupings of biological traits. We focus on trait groupings that describe three important benthic ecosystem properties, namely bioturbation, community stability, and juvenile dispersal. Recognizing that groups of traits interact and are constrained within an organism, we statistically define important functional trait subgroups that describe each ecosystem property. The sub‐groups are scored according to their weighted ecological impact to gain an overall estimation of the cumulative expression of each ecosystem property at individual sites. Furthermore, by assigning each property a value relative to its observed maximum, and by summing up the individual property values, we offer an estimate of benthic ecosystem multifunctionality. Based on a spatially extensive benthic data set, we were able to identify coastal areas with high and low potential for the considered benthic ecosystem properties and the measure of ecosystem multifunctionality. Importantly, we show that a large part of the spatial variation in functional trait sub‐groups and in benthic ecosystem multifunctionality was explained by environmental change. Our results indicate that through this simplification it is possible to estimate the functionality of the seafloor. Such information is vital in marine spatial planning efforts striving to balance the utilization with the preservation of natural resources.